Effect of a common exercise programme with an individualised progression criterion based on the measurement of neuromuscular capacity versus current best practice for lower limb tendinopathies (MaLaGa trial): a protocol for a randomised clinical trial - Escriche-Escuder, Adrian; Cuesta-Vargas, Antonio; Casaña Granell, José (BMJ Open, 2021)
Introduction: High-load resistance training has shown positive effects in pain and function in lower limb tendinopathies. However, some authors suggest that current exercise programmes produce an increase in tolerance to load and exercise in general but without fixing some existing issues in tendinopathy. This may indicate the need to include training aspects not currently taken into account in the current programmes. The main objective of this study will be to compare the effect of a common exercise protocol for the three predominant lower limb tendinopathies (Achilles, patellar and gluteal), based on an individualised control of the dose and training of specific aspects of the neuromuscular system versus the current best practice for each location. Methods and analysis: This study will be conducted among people with mid-portion Achilles, patellar or gluteal tendinopathy. The participants allocated to the experimental group will perform a 14-week innovative common therapeutic exercise programme. Participants allocated to the control group will carry out a 14-week exercise programme based on the best current practice for each of the studied locations. The Victorian Institute of Sports Assessment questionnaire will be considered the primary outcome. Pain, central sensitisation, fear avoidance behaviour, quality of life, treatment satisfaction, lower-limb strength and function, and high-density electromyography profile will be evaluated as secondary outcomes. Outcomes will be assessed at baseline, 7 weeks, after the intervention (week 14), 26 weeks and 52 weeks. Ethics and dissemination: The study has been approved by the Portal de Ética de la Investigación Biomédica de Andalucía Ethics Committee (1221-N-19). All participants will be informed about the purpose and content of the study and written informed consent will be completed. The results of this study will be published in a peer-reviewed journal and will be disseminated electronically and in print.
Keywords: Ejercicio físico - Uso terapéutico; Tendones - Enfermedades; Foot and ankle; Hip; Knee; Rehabilitation medicine; Sports medicine